Need of the hour, “health literacy”: the drug of choice for the current pandemic - Vaishnav, Kritika; Galhotra, Abhiruchi; Raj, Utsav; Rai, Nidhi (International Journal Of Community Medicine And Public Health, 2020)
COVID-19 was officially declared a pandemic by World health organization on 11 March 2020. The most effective ways to protect yourself and others against COVID-19 are non-pharmacological methods. Therefore, prevention and supportive care are highly recommended so health literacy going to play an important role in preventing the diseases. It implies to the achievement of a level of knowledge, personal skills and confidence to take action to improve personal and community health by changing personal lifestyles and living conditions. Health literacy is still new and there is a paucity of published literature, there are few studies have demonstrated its effectiveness, many countries with good literacy have got good success in controlling this pandemic, for example Kerala in India. This demonstrated that education can support the weak and overburden health systems in successfully mitigating the effect of this global pandemic where the treatments and vaccines for it are in the development phase.